Pembelajaran Temuan Terbimbing Berbantuan Manik Android: Motivasi dan Hasil Belajar Operasi Hitung Bilangan Bulat - Gede Putra Astawa, I Gusti Lanang (Jurnal Didaktika Pendidikan Dasar, 2018)
An instructional media using Smartphone Android Beads smartphone was innovated to increase students’ motivation and learning outcomes on integer counting operations. Learning mathematics with Android beads has many advantages compared to ordinary beads for its durability, ease to carry, ease to use by students, and the unlimited number of beads to use. Employing the guided discovery learning, the media was used for 35 sixth graders. The effort was successful to increase the pupils’ motivation and learning outcomes. Ten steps were taken to produce Android bead learning media. ARCS questionnaires were used to measure the pupils’ motivation, and integer operating tests to measure students’ learning outcomes. It was found out that concerning motivation with a score range of 0-5, the students’ attention increased to 4.6; relevance to 4.1; confidence and satisfaction were respectively 4.6 and 80.0. The average value of pupils’ learning outcomes reached 80.0 with a total mastery learning of 88.57%.